Analysis of Microleakage in Different Composite Resin Systems - Abuzenada, Basem Mohammed (Bangladesh Journal of Medical Science, 2025)
Background Microleakage is a critical factor in the long-term success of dental restorations, particularly in composite resin systems. It can lead to postoperative sensitivity, secondary caries, and eventual failure of the restoration. Different composite resin systems may exhibit varying degrees of microleakage due to differences in their composition, polymerization techniques, and adhesive systems. The purpose of this study is to analyze the microleakage in different composite resin systems. Materials and Methods In this in-vitro study, 60 extracted human molars were prepared with standardized Class V cavities. The teeth were randomly divided into three groups (n=20) based on the composite resin system used: Group A (nanohybrid composite), Group B (microhybrid composite), and Group C (bulk-fill composite). A standardized bonding procedure was followed for all samples. After placement of the restorations, the samples were thermocycled for 500 cycles between 5°C and 55°C. The teeth were then immersed in a 2% methylene blue dye solution for 24 hours to assess microleakage. Following dye penetration, the teeth were sectioned and examined under a stereomicroscope for dye penetration at both the occlusal and gingival margins. Microleakage scores were recorded using a 0-3 scale, with 0 indicating no leakage and 3 indicating maximum leakage. Results The results showed significant differences in microleakage between the composite resin systems. Group A (nanohybrid composite) showed the least microleakage, with an average score of 0.75 ± 0.5, while Group B (microhybrid composite) exhibited moderate microleakage, with an average score of 1.25 ± 0.6. Group C (bulk-fill composite) demonstrated the highest microleakage, with an average score of 2.0 ± 0.8. Statistical analysis using ANOVA revealed a significant difference between the groups (p < 0.05), with Group A performing better in terms of microleakage resistance. Conclusion The study concludes that nanohybrid composite resin exhibits superior performance in preventing microleakage compared to microhybrid and bulk-fill composite systems. This may be attributed to the smaller particle size and better polymerization properties of the nanohybrid composite. Clinicians should consider these differences when selecting materials for restorative procedures to minimize the risk of microleakage and enhance the longevity of restorations. BJMS, Volume: 24. Supplementary Issue 2025, Page : 95-98